2021
DOI: 10.3389/fpsyg.2021.566517
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of the Relationship Between Happiness and the Rise of Media Consumption During COVID-19 Confinement

Abstract: The confinement of the population into their homes as a result of COVID-19 has entailed a notable increase in the consumption of diverse media. This exploratory study aimed to examine how the increase in media consumption was related to subjective happiness and psychological well-being. For this purpose, a questionnaire was administered to a sample of Spanish adults (n = 249; 53.8% women; aged between 18 and 75, Mage = 42.06, SD = 12.37) to assess their consumption of different media before and during confinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…We also found that the frequency of SNS usage was significantly associated with overall life satisfaction, exhibiting a J-curve phenomenon (three to four times per week was better than everyday use). In other recent research, higher SNS consumption showed a negative correlation with happiness levels in Europe [19]. However, this does not directly contradict our current findings, as Japanese SNS consumption patterns tend to differ from those seen in other countries [20].…”
Section: Discussioncontrasting
confidence: 51%
“…We also found that the frequency of SNS usage was significantly associated with overall life satisfaction, exhibiting a J-curve phenomenon (three to four times per week was better than everyday use). In other recent research, higher SNS consumption showed a negative correlation with happiness levels in Europe [19]. However, this does not directly contradict our current findings, as Japanese SNS consumption patterns tend to differ from those seen in other countries [20].…”
Section: Discussioncontrasting
confidence: 51%
“…The fact that similar increases were reported for many other domestic activities-like watching news and movies, calling friends, cooking, cleaning, and sleeping (Fink et al, 2021;Muñiz-Velázquez et al, 2021;Ziv & Hollander-Shabtai, 2021)-raises the pertinent question whether changes in musical habits were merely an epiphenomenon of home confinement. Survey studies on qualitative motivations for engagement and perceived coping efficacy of music suggest that this was not the case.…”
Section: Coping Efficacymentioning
confidence: 71%
“…Relatedly, Krause et al (2021) found that life satisfaction was positively associated with music listening, but negatively associated with watching TV/videos/movies at the within-person level. Equivalent negative associations emerged between watching TV and eudaimonic as well as hedonic well-being (Muñiz-Velázquez et al, 2021). While most people experienced equally strong emotions in response to music during lockdown compared to before, increases were slightly more frequent than decreases-but this was also the case for non-music-induced emotions (Ziv & Hollander-Shabtai, 2021).…”
Section: Coping Efficacymentioning
confidence: 88%
See 2 more Smart Citations